Squamous Cell Carcinoma in Patients with Inherited Epidermolysis Bullosa: Review of Current Literature - Domenico Bonamonte; Angela Filoni; Aurora De Marco; Lucia Lospalluti; Eleonora Nacchiero; Valentina Ronghi; Anna Colagrande; Giuseppe Giudice; Gerardo Cazzato (2022)
Epidermolysis bullosa (EB) is a group of rare congenital diseases caused by mutations in structural proteins of the dermal/epidermal junction that are characterized by extreme epithelial fragility, which determines the formation of bullae and erosions either spontaneously or after local mechanical traumas. In EB patients, skin fragility leads to many possible complications and comorbidities. One of the most feared complications is the development of cutaneous squamous cell carcinomas (SCCs) that particularly in the dystrophic recessive EB subtype can be extremely aggressive and often metastatic. SCCs in EB patients generally arise more often in the extremities, where chronic blisters and scars are generally located. SCCs represent a big therapeutic challenge in the EB population. No standard of care exists for the treatment of SCC in these patients, and therapy is based on small case studies. Moreover, the pathogenesis of cSCC in EB patients is still unclear. Many theories have been indeed postulated in order to explain why cSCC behaves so much more aggressively in EB patients compared to the general population. cSCC in EB seems to be the result of many complex interactions among cancer cells, skin microenvironment, susceptibility to DNA mutations and host immune response. In this review, we analyze the different pathogenetic mechanisms of cSCC in EB patients, as well as new therapies for this condition.